The principles of teaching foreign professionally-oriented communication of future navigators - Костюк, Вікторія (Pedagogy of Higher and Secondary Education, 2014)
Kostiuk V. B. The principles of teaching foreign professionally-oriented communication of future navigators. The article deals with the principles of teaching foreign professionally-oriented communication of future navigators, which implementation will provide a high professional standard of the future experts.